Infective endocarditis: a case series - Yazid, Keyshia Nur; Bermansyah; Satria, Gama; Umar, Ahmat; Nugraha, Aswin; Tobing, Arie Hasiholan Lumbang; Nasution, Indra Hakim (Indonesian Vascular Access Association (IVAA), 2024)
Introduction: Infective endocarditis (IE) remains a critical cardiovascular condition with significant mortality rates, ranging from 20% during hospitalization to 25-30% within six months post-infection. Valve abnormalities have been strongly associated with IE and worsen patient symptoms and prognostic. This study presents a case series of IE in Dr. Mohammad Hoesin Palembang Hospital. Case presentations: This case series reports on the management and outcomes of four pediatric patients treated for IE between January and May 2024 in RSUP Mohammad Hoesin Palembang. Each patient presents with moderate to severe mitral regurgitation and valve vegetation. Diagnoses were based on clinical symptoms and echocardiographic findings, adhering to the Duke criteria. The management involved systemic antibiotics and valve replacement surgery, with a focus on individualized treatment plans based on the severity of regurgitation and the presence of vegetation. Notably, all four patients survived and demonstrated substantial improvement in quality of life after surgical management. Conclusions: Our findings emphasize the efficacy of a multidisciplinary approach combining antibiotic therapy with timely surgical intervention for successful treatment outcomes in IE. Early diagnosis and appropriate management, including valve replacement, when necessary, are crucial for improving patient survival and quality of life.